Investigation of Martian Magnetic Topology Response to 2017 September ICME. Issue 15 (14th August 2018) - Xu, Shaosui; Fang, Xiaohua; Mitchell, David L.; Ma, Yingjuan; Luhmann, Janet G.; DiBraccio, Gina A.; Weber, Tristan; Brain, David; Mazelle, Christian; Curry, Shannon M.; Lee, Christina O.
Abstract: Many aspects of the Sun‐Mars interaction have been investigated during solar transient events with measurements from multiple spacecrafts and also simulation efforts. Limited discussion has been paid to magnetic topology response to disturbed upstream conditions. The implications of topology changes include, but are not limited to, the pattern of energetic particle precipitation into the Martian atmosphere and the impact on cold ion escape during solar transient events as low‐energy ion escape is dependent on magnetic topology. In this study, we investigate the magnetic topology response to the 2017 September interplanetary coronal mass ejection (ICME) event with measurements collected by the Mars Atmospheric and Volatile EvolutioN spacecraft. It is found that the interface between draped interplanetary magnetic field and closed field lines was moved from 800–1400 km in altitude during quiet conditions to 200–400 km after ICME arrived at Mars and then relaxed back to high altitudes again after the event. To gain insight into magnetic topology response on a global scale, we first validate magnetic topology from a time‐dependent simulation with a single‐fluid multispecies magnetohydrodynamic (MHD) model by comparing magnetic topology determined from Mars Atmospheric and Volatile EvolutioN data, which shows a good agreement. Then we present MHD predictions of global magnetic topology changes during this ICME event. In addition to a deeper interplanetary magnetic field penetration, MHD results suggest more open field lines in response to the ICME event. Plain Language Summary: An important way for Mars to lose its atmosphere over time is through solar wind striping away ions from Mars. The planet lacks of an intrinsic global magnetic field but possesses localized crustal fields so that solar wind and the interplanetary magnetic field have direct access to the Martian ionosphere. This effect is intensified when a coronal mass ejection is emitted from the Sun and hits Mars. Charged particles subject to electromagnetic forces so that the magnetic topology, whether a magnetic field line connects to Mars and/or solar wind, is an important aspect of the Sun‐Mars interaction and also closely related to energy and particle transport at Mars and low‐energy ion escape. In this study, we investigate how the Martian magnetic topology responds to the coronal mass ejection event occurred in September 2017 with measurements from the Mars Atmosphere Volatile and Evolution spacecraft and also simulation results from a magnetohydrodynamic model. It is found that during the event, interplanetary magnetic field penetrates deeper into the atmosphere and also there are more magnetic field lines connecting Mars and solar wind, which means ions subject to escape starting from lower altitudes, where ion densities are higher. Key Points: From MAVEN data, IMF is found to penetrate deeper over the northern hemisphere due to enhanced solar wind dynamic pressure during the ICME Topology from MHD shows a good agreement with data and provides insights into a global response MHD results suggest deeper IMF penetration and more open field lines during the ICME event